260-LB: Continuous Glucose Monitoring Metrics in Islet Transplant Recipients with Long-Term Insulin Independence - BAIDAL, DAVID; ALVAREZ GIL, ANA M.; PADILLA, NATHALIA; RICORDI, CAMILLO; ALEJANDRO, RODOLFO (Diabetes (New York, N.Y.), 2019)
Continuous glucose monitoring (CGM) following islet transplantation (ITx) has shown improved time-in-range, reduced glycemic variability (GV) and hypoglycemia prevention despite subnormal beta-cell function. However, it is unclear if improvement by CGM persists long-term in insulin independent (Ifree) ITx recipients. We evaluated 5 ITx recipients who remained Ifree for >5 years. Subjects completed 7-day non-blinded CGM (Dexcom G4 Platinum). HbA1c, 90min C-peptide, Clarke score, and BETA-2 score (composite measure of beta-cell function after ITx) were obtained. Before ITx, mean age was 47.2±4.0 years, diabetes duration 34.6±9.4 years, HbA1c 7.0±1.2%, insulin/Kg/day 0.44±0.08 units and Clarke score 5 (range 4-7). Subjects received 1-2 islet infusions. Induction immunosuppression consisted of ATG or daclizumab and dual maintenance with sirolimus, tacrolimus or mycophenolate mofetil. At time of CGM, subjects were Ifree and 10.7±3.5 years post-ITx (range 7.7-16.0). Two subjects were on non-insulin adjunct therapies. CGM and metabolic data, BETA-2 and Clarke scores are shown in Table 1. In Ifree ITx recipients with very good long-term graft function (BETA-2 score>15) and restoration of hypoglycemia awareness, CGM shows near-normalization of time-in-range and GV with minimal time-in-hypoglycemia. ITx is a successful long-term cellular therapy for T1D in a selected group of patients.